IMPACT OF IMPROVED SEEDS AND SOME MODERN TECHNOLOGIES ON INCREASING THE SUPPLY OF WHEAT CROP IN IRAQ FOR THE AGRICULTURAL SEASON 2019-2020 - Abdul Rahman T. F.; Osamah K. J; Bilal N. J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This research was aimed to study the impact of modern technologies represented by (High-productivity improved seeds, fertilizer of leaves, Atlantis pesticide) on increasing production both quantitatively and qualitatively. The importance of the research comes from take a set of programs and use some modern technologies in order to increase the productivity of the donum for the purpose of vertical increase of production per unit area. The problem of the research was the low rate of wheat crop productivity for Iraq compared to global productivity rates, and given the importance of achieving self-sufficiency in wheat from local production due to the decreasing global stockpile, high supply prices and low local production in the past years with limited available resources. A set of programs have been taken and some modern technologies have been introduced in order to increase the productivity of the donum and achieve the vertical increase of production per unit area through the program to enhance food security. The Harry, Ayer & Edward Schuh model was used in order to measure the degree of transition of the supply function of the program fields compared to the traditional fields, in order to estimate the relative transition coefficient in the supply function resulting from the technical change represented by the adopting of modern technologies from this crop, as the results of the analysis showed that modern technologies lead to a shift in the supply function by (2.9-8.04-5.3%) for the three improved wheat varieties, respectively. The results also showed the presence of a large waste of the water resource that led to a negative impact on the production.